Does ASEAN matter? a view from within - Natalegawa, Marty (ISEAS-Yusof Ishak Institute, 2018)
Natalegawa offers a unique insider-perspective on the present and future relevance of ASEAN. It is about ASEAN's quest for security and prosperity in a region marked by complex dynamics of power. Namely, the interplay of relations and interests among countries--large and small--which provide the settings within which ASEAN must deliver on its much-cited leadership and centrality in the region.